Architecture and Participation in Civic Life: Rabin Square, Tel Aviv - Hatuka, Tali (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2005)
This paper presents an interdisciplinary framework for the study of relationships between architecture and participation in civic life. It examines the formal attributes of a public place - Rabin Square, Tel Aviv - and its use for civil practices. The paper demonstrates the ways in which, over several decades, architectural intervention in the square and socio-political processes taking place in Israel have led to the ossification of patterns of civil assembly. Those patterns, in turn, create an illusion of active participation in democratic life.